2019
DOI: 10.1016/j.ymgmr.2019.100470
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genetic copy number variants of the human GLUT3 glucose transporter gene SLC2A3 on protein expression, glycolysis and rheumatoid arthritis risk: A genetic replication study

Abstract: Objectives The gene encoding glucose transporter 3 (GLUT3, SLC2A3 ) is present in the human population at variable copy number. An overt disease phenotype of SLC2A3 copy number variants has not been reported; however, deletion of SLC2A3 has been previously reported to protect carriers from rheumatoid arthritis, implicating GLUT3 as a therapeutic target in rheumatoid arthritis. Here we aim to perform functional analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Whether GLUT3 protein expression reflects this increased transcription in duplication carriers remains controversial. To date, only a single study by Vittori et al (2014) found increased protein expression in cell lines from duplication carriers, whereas we and others did not observe such an effect in similar experimental settings (Merker et al, 2017; Simpfendorfer et al, 2019). Furthermore, the duplication variant did not affect glucose uptake levels in lymphoblastoid cells under basal conditions (Merker et al, 2017).…”
Section: The Glucose Transporter Glut3contrasting
confidence: 59%
See 2 more Smart Citations
“…Whether GLUT3 protein expression reflects this increased transcription in duplication carriers remains controversial. To date, only a single study by Vittori et al (2014) found increased protein expression in cell lines from duplication carriers, whereas we and others did not observe such an effect in similar experimental settings (Merker et al, 2017; Simpfendorfer et al, 2019). Furthermore, the duplication variant did not affect glucose uptake levels in lymphoblastoid cells under basal conditions (Merker et al, 2017).…”
Section: The Glucose Transporter Glut3contrasting
confidence: 59%
“…These data suggest that SLC2A3 may provide a protective effect against RA. However, in a higher‐powered independent replication study, this association was not observed (Simpfendorfer et al, 2019). Although initial results may have been a false positive, it is also possible that there is a population‐specific effect of SLC2A3 CNVs on different disease phenotypes (Merker et al, 2017).…”
Section: Slc2a3 Copy Number Variation and Associated Clinical Phenotypesmentioning
confidence: 97%
See 1 more Smart Citation
“… 50 Interestingly, deletion of SLC2A3 the gene encoding GLUT3 can prevent RA-related joint injuries, indicating that as a glycolysis-related protein GLUT3 is a potential therapeutic target for RA. 51 It is apparent that up-regulation of either HKs or GLUT would facilitate glycolysis. Indeed, HK2 and GLUT are highly expressed in RA synovium, which is believed to be a driving force for the enhanced migration and invasion ability of FLSs.…”
Section: Involvement Of Energy Metabolism Alteration In Ramentioning
confidence: 99%
“…There are only a few reports on GLUT1, GLUT3 and GLUT4 in RA. Heterozygous deletion of GLUT3 correlates directly with expression levels of GLUT3 and influences glycolysis rates in the human immune system ( 46 ), but the frequency of the GLUT3 copy number variant is not different among RA, multiple sclerosis and heathy control, providing no evidence for RA protection in deletion of GLUT3 ( 46 ), the study of which demonstrated GLUT3 is not necessary for glucose transfer in patients with RA. However, another study showed the mutual activation between CD4 + T cells and FLS, which resulted in increased proliferation and expression of glucose transporters GLUT1 and GLUT3 in FLS ( 47 ).…”
Section: Glucose Metabolism As An Arthritogenic Risk Factormentioning
confidence: 99%